Siapakah yang harus memaklumkan hal-hal kesihatan kepada orang ramai - pakar perubatan atau pihak media? - Fuziah Kartini Hassan Basri, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
Health information is a specific type of information, hence requires expert and credible sources from the relevant field. The health or medical expert however, is often criticized as lacking sensitivity toward the ordinary person who is no expert and finds it difficult to understand medical jargon. Like most technical and specialized experts, the medical experts are close to their field which is filled with technical and academic concepts which are usually alien and strange to the personin- the-street. If the medical experts failed to reach the people comprehensibly, then health and medical information will not be diffused in society. It is here that the mass media must be recognized as a solution to the problem. The mass media are channels of information quite easily and rather cheaply accessed by the people. In this infomedia era, the position and function of the mass media is synonymous with knowledge and information. The media are mass and ubiquitous channels; without them, it is difficult to disseminate information in society, thus the people will not be empowered to make decisions. Media have also been proven to be successful and influential channels reaching the people with a myriad of information in comprehensible language and audience-friendly manner. Therefore the question of who should communicate health matter to the public - medical or media man, should not arise because there is clearly a symbiotic relationship between them: media, like its name suggests, are credible intermediaries that can be utilized by medical experts to communicate health matter to the public, whilst the media need to refer to medical experts to obtain health and medical information. In a nutshell medical and media persons must synergistically work together for the good of the people.